Kredibilitas Pengasuhan Ibu : Reinterpretasi Hadith Anta Ahaqqu Bihi Ma Lam Tankihi dalam Perspektif Maqashid al-Syari’ah - Mahdalena Nasrun (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2025)
After divorce, conflicts often arise related to the division of property, alimony, and childcare (hadhanah). Although the right to raise children has been normatively given to the mother in accordance with the textual hadith anta ahaqqu bihi ma lam tankihi. However, in reality, custody of the child is given to the father. This reality shows that there is a transfer of custody to the father due to the doubtful credibility factor of the mother. This research aims to understand the hadiths of childcare in the perspective of maqashid al-shari'ah. The research method used is qualitative with a content analysis approach. The results of the study show that there are three themes in parenting. The narration of the first hadith by Abu Dawud and Ahmad about childcare is given to a mother of saheeh quality. The second hadith narrated by Abu Dawud, an-Nasai and ad-Darimi is considered saheeh by the Judge. The third hadith narrated by Abu Dawud, an-Nasai and Ahmad regarding the right to choose for children in parenting is considered saheeh by the Judge. Through the consideration of maqashid al-shari'ah; hifzh ad-din; Hifzh Al-Nasl for the benefit of children, then post-divorce child care is no longer rigid on one side, but focuses on who better guarantees the best interests of the child for his future. The hadith signal that allows children to choose is interpreted as a preventive effort so that children are not psychologically depressed and their rights are protected.